Screening for late‐onset Pompe disease in undiagnosed myopathies. Issue 2 (8th November 2016) - Matsui, Misa; Inoue, Kimiko; Sakoda, Saburo; Matsumura, Tsuyoshi; Hamazaki, Takashi; Kosuga, Motomichi; Okuyama, Torayuki; Shimada, Yohta; Ohashi, Toya; Nishino, Ichizo
Abstract: Background: Pompe disease is caused by a deficiency of acid alpha‐glucosidase. Its prevalence varies depending on ethnicity, and is less prevalent in Japan as compared with other countries. Because of the wide spectrum of clinical features in late‐onset cases, some patients might be misdiagnosed with another myopathy, thus the actual prevalence in Japan might not be accurately reported. Aim: To clarify the actual prevalence of late‐onset Pompe disease, we investigated acid alpha‐glucosidase activity in patients with undiagnosed myopathies. Methods: Of 42 patients with undiagnosed myopathies, 41 underwent assessment of acid alpha‐glucosidase enzyme activity using dried blood spot analysis. As a second step, reassessment of acid alpha‐glucosidase activity was carried out using cultured skin fibroblasts. We also determined acid alpha‐glucosidase activity in biopsied muscle tissue obtained from the one other patient, who had previously undergone a muscle biopsy. Finally, gene analysis was carried out to confirm diagnosis. Results: Four patients showed reduced acid alpha‐glucosidase activity in dried blood spot findings, of whom one possessed a pseudo‐deficiency allele. Furthermore, one patient who showed reduced acid alpha‐glucosidase activity in a biopsied muscle specimen was diagnosed with late‐onset Pompe disease based on gene analysis. Conclusions: Of the present 42 patients, only one patient was diagnosed with late‐onset Pompe disease. The prevalence of Pompe disease in Japan does not seem to be as high as in other countries, though a certain number of patients might exist among those with undiagnosed myopathies. A larger and more systematic survey is necessary to elucidate the actual prevalence of late‐onset Pompe disease in Japan.